Value-ology : Aligning sales and marketing to shape and deliver profitable customer value propositions /: Aligning sales and marketing to shape and deliver profitable customer value propositions. (2017) - Kelly, Simon; Johnston, Paul; Danheiser, Stacey
No abstract available